(untitled) (diségno, 2019)
The issue proposed in the call ‘The representation of landscape, territory and environ ment’ is placed in the crossing of various disciplines: geography, ecology, urban design, architecture, but also social sciences and humanities, till to include the latest interdisciplinary exchange between life sciences and techniques which is on the basis of computation. (read more)